2013
DOI: 10.1177/039463201302600404
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Low Dose Canine Endotoxemia Model to Test Anti-Inflammatory Drugs: Effects of Prednisolone

Abstract: Infusion of low doses of lipopolysaccharide (LPS) in human volunteers provides a standardised model to study novel anti-inflammatory drugs. However, low dose endotoxemia is not well characterised in animals larger than rodents and trials with immunomodulating substances are scarce. We conducted a dose-finding study to establish a canine endotoxemia model combining optimal cytokine response with minimal burden for the animals. We thereafter evaluated the pharmacodynamics and pharmacokinetics (PK) of prednisolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We showed that the liposomal formulation further improved the tolerance profile of the detoxified LPS characterized by a significant decrease of its inflammatory activity and reduction of its pyrogenic activity by a factor 10. In addition, while LPS were described to induce severe sepsis symptoms at 0.1 to 2µg/kg doses ( 52 , 53 ), F2Lipo-MP-LPS was found to be well tolerated in dogs in intravenous administration up to 10µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the liposomal formulation further improved the tolerance profile of the detoxified LPS characterized by a significant decrease of its inflammatory activity and reduction of its pyrogenic activity by a factor 10. In addition, while LPS were described to induce severe sepsis symptoms at 0.1 to 2µg/kg doses ( 52 , 53 ), F2Lipo-MP-LPS was found to be well tolerated in dogs in intravenous administration up to 10µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…More than 35 years ago, some pharmacokinetic reports were published (1)(2)(3)(4). More recently, prednisolone concentration-time data have been made available but without thorough PK-analyses (5,6). The PK studies cited above were performed on few dogs and since then technical improvements have made the analytical techniques for drug quantification in plasma more sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was also described in a canine endotoxemia model. Treatment with prednisolone attenuated IL-6 and TNF α concentrations dose-dependently [ 105 ]. Furthermore, the chemokine CCL17 was significantly increased in dogs with canine atopic dermatitis.…”
Section: Resultsmentioning
confidence: 99%